1995
DOI: 10.1016/s0194-5998(95)70077-3
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of p53 predicts organ preservation using induction chemotherapy and radiation in patients with advanced laryngeal cancer

Abstract: A critical research frontier in head and neck oncology involves defining the use of induction chemotherapy regimens to allow organ preservation and to avoid functionally debilitating surgical resections. Completed clinical trials in laryngeal cancer indicate that such an approach is feasible, but progress thus far has been limited by our inability to predict which patients are likely to respond to chemotherapy and preserve their larynx. Mutation of the p53 tumor-suppressor gene is the most common genetic alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
1
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 7 publications
3
63
1
3
Order By: Relevance
“…Interestingly, a review of their gene list reveals increased expression of some NF-nB regulated genes identified in our previous murine SCC and our present study in cluster B, in the subset associated with the inactivation of TP53 and greater malignant potential. In another study by Bradford et al (16,17), wt TP53 genotype with low TP53 protein expression has been associated with cisplatin resistance in vitro and chemoradiation resistance in patients. This was shown to be inversely related to the expression of BCL-xL (61), another gene which we have shown to be coregulated by NF-nB as well as STAT3 (19).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, a review of their gene list reveals increased expression of some NF-nB regulated genes identified in our previous murine SCC and our present study in cluster B, in the subset associated with the inactivation of TP53 and greater malignant potential. In another study by Bradford et al (16,17), wt TP53 genotype with low TP53 protein expression has been associated with cisplatin resistance in vitro and chemoradiation resistance in patients. This was shown to be inversely related to the expression of BCL-xL (61), another gene which we have shown to be coregulated by NF-nB as well as STAT3 (19).…”
Section: Discussionmentioning
confidence: 93%
“…The mutation or loss of expression of TP53 has been implicated in a decrease in programmed cell death (14,15). Interestingly, HNSCC retaining wt TP53 genotype but weakly expressing TP53 protein are associated with greater resistance to chemotherapy and/or radiation than those expressing mutant TP53 in clinical trials and studies in vitro (16,17). However, the molecular basis for this observation and possible relationship to expression of various other genes previously associated with differences in malignant potential is not fully understood.…”
mentioning
confidence: 99%
“…Both chemotherapy and radiotherapy have had a significant impact on the treatment of OSCC (17,18). Specifically, neoadjuvant CF therapy is now considered standard treatment for OSCC (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, levels of p53 can be stabilized by interactions with other intracellular proteins such as mdm-2, leading to positive immunostaining (35,36). Second, certain p53 mutations may result in very high levels of p53 protein that may have some residual activity in regulating cellular functions (37,38). Third, p53 point mutations resulting in a stop codon, frameshift, or nonsense mutations may result in altered or truncated proteins that are not detected by immunohistochemistry (39).…”
Section: Loss Of P16mentioning
confidence: 99%